PENGARUH PROGRAM PERKULIAHAN BIOLOGI KONSERVASI DENGAN PENDEKATAN KONTEKSTUAL BERBASIS KEARIFAN LOKAL ACEH TERHADAP PENINGKATAN LITERASI LINGKUNGAN - Evi Apriana, (Jurnal Serambi Ilmu, 2024)
This study aimed to collect information relating to the influence of conservation biology lecture program through Acehnese local wisdom-based contextual approach to improving the environmental literacy. The study was conducted using Quasi Experiment design with One Group Pretest-Postest Design and involved a number of students (n = 33) of the VI semester who opted Conservation Biology course as a research subject. One group was given pretest and postest. The tests were used to measure the environmental literacy based on six components and 40 sub-components of environmental literacy. Experimental groups were treated with conservation biology course through Acehnese local wisdom-based contextual approach. Qualitative data analysis techniques derived fromdirect observations and analyzed descriptively, while quantitative data were obtained from the pre-test and post-test score, analyzed using excel program and statistical tests through normalized gain. From the pretest, posttest, and learning observations, it was obtained that conservation biology lecture program through Acehnese local wisdom-based contextual approach can improve the environmental literacy of students. Improved learning outcomes occurred in the superior, medium, and low group, in all components of environmental literacy and all sub-components in the components of environmental literacy. The largest increased learning outcomes were seen in the component of cognitive skills while the smallest was showed in the components of knowledge regarding environmental issues, problems and measures (environmentally responsibled behavior).